Factors Affecting Reading Performance Of Primary Four School Children: The Case Of University Practice School (South Campus) Winneba, Ghana. - Evelyn Susuana Ayorkor Asumang (Noyam Journals, 2020)
This study examines the inhibiting factors affecting reading as a medium of instruction for primary four pupils in the University Practice Primary School (UPPS) at Winneba. Unfortunately, reading which is supposed to be a medium of communication had rather become a challenge by the aforementioned pupils. In this study, both quantitative and qualitative designs have been applied to address this gap. The findings of the study revealed that out of the thirty-two pupils tested, using the 100 high-frequency words for word recognition, only four (4) pupils attained a mastery level of 80%. Thus, rendering the remaining pupils as poor readers. The study recommends that pupils with reading difficulties may need more periods on the academic time table to read in order to overcome their problems. Furthermore, teachers must give much attention to pupils with such challenges.